Transferências intergovernamentais e a equalização fiscal nos municípios - Rodrigues, Marina Branquinho (2017)
This dissertation proposes and tests a new model for the intergovernmental fiscal transfers system from Federal Government to municipalities, based on fiscal equalization, considering both the capacity and the fiscal need of these local governments. It carried out an empirical research, using data from the Demographic Census and Brazilian tax data for the application of fiscal equalization models based on the international literature of fiscal federalism. The results show that when applying an intergovernmental transfer system focused on the fiscal equalization of the municipalities, considering their capacity and the fiscal need, there is a loss of resources by the Southeast region and a direction for the northeast region. It also identifies gains in resources, especially for small municipalities, with up to ten thousand inhabitants and considerable losses for municipalities with a population between fifty and five hundred thousand inhabitants. Oil producing municipalities, regardless of their resident population, are the ones that lose the most resources, given their high volume of transfers receipts due to royalties